Educating Europe - Panu Poutvaara (Center for Economic Studies and ifo Institute (CESifo), 2004)
The mobility of labor reduces national incentives to invest in internationally applicable education. The European Union could overcome this by allowing member states to institute graduate taxes or income-contingent loans, collected also from migrants. This paper presents calculations on how a graduate tax system could look for Finland. To protect citizens against Leviathan governments, graduate taxes or income-contingent loans could be based on voluntary contracts. Education would then be financed publicly only for those accepting also to share the returns. With EU enlargement, such reforms could generate a triple dividend.
Keywords: F22; H24; H52; I28; 330; graduate taxes; European Union; individual accounts; income-contingent loans; migration